ANALYSIS OF FACTORS AFFECTING THE YIELD OF BONDS AS AN INVESTMENT INSTRUMENT (World Bulletin of Management and Law, 2024)
In this state, the importance of bonds and the use of financial resources, the formation of the market price of bonds and factors, the investor's profitability and the market have been studied. A detailed scientific study of the risk associated with sovereign credit ratings, inflation, interest rates, bond repayment terms and exchange rates as basic factors, the investor's expected return on the bond. Information in the state is analyzed and analyzed on primary bonds, issued Eurobonds to Uzbekistan, Singapore and Australia and international stock markets.